2009
DOI: 10.1116/1.3231480
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for plasma etching of HfO2 gate stacks with Si selectivity and photoresist trimming

Abstract: Articles you may be interested inComparison of the effects of downstream H2-and O2-based plasmas on the removal of photoresist, silicon, and silicon nitride Effect of high-frequency variation on the etch characteristics of ArF photoresist and silicon nitride layers in dual frequency superimposed capacitively coupled plasmaa) Plasma enhanced chemical vapor deposition Si-rich silicon oxynitride films for advanced self-aligned contact oxide etching in sub-0.25 μm ultralarge scale integration technology and beyond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Their models were actively adopted to predict feature scale profiles of planar-type Si gate, Si fin of FinFET, trench, and hole etching for various kinds of films and plasmas such as Si (Cl 2 ∕Ar mixture), SiO 2 , SiN (C 2 F 6 , CHF 3 , and C 4 F 8 ∕O 2 ∕Ar mixtures), SiOCH (He∕H 2 and Ar∕O 2 mixtures), and HfO 2 (Ar∕BCl 3 ∕Cl 2 and Ar∕O 2 mixtures). [51][52][53][54][55][56][57][58][59] As for HARC etching, the mechanism of the 3D SiO 2 HARC feature distortion during C 4 F 8 ∕O 2 ∕Ar plasma etching with a CCP reactor was discussed in the cases of symmetric and asymmetric patterns (AR ¼ 40) considering the charging effect caused by ion scattering and charge mobility on the pattern surface with the polymer. 60 The radius and depth, including the photoresist mask of the HARC pattern, were 25 and 2670 nm, respectively.…”
Section: Cell Removable or Voxel Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their models were actively adopted to predict feature scale profiles of planar-type Si gate, Si fin of FinFET, trench, and hole etching for various kinds of films and plasmas such as Si (Cl 2 ∕Ar mixture), SiO 2 , SiN (C 2 F 6 , CHF 3 , and C 4 F 8 ∕O 2 ∕Ar mixtures), SiOCH (He∕H 2 and Ar∕O 2 mixtures), and HfO 2 (Ar∕BCl 3 ∕Cl 2 and Ar∕O 2 mixtures). [51][52][53][54][55][56][57][58][59] As for HARC etching, the mechanism of the 3D SiO 2 HARC feature distortion during C 4 F 8 ∕O 2 ∕Ar plasma etching with a CCP reactor was discussed in the cases of symmetric and asymmetric patterns (AR ¼ 40) considering the charging effect caused by ion scattering and charge mobility on the pattern surface with the polymer. 60 The radius and depth, including the photoresist mask of the HARC pattern, were 25 and 2670 nm, respectively.…”
Section: Cell Removable or Voxel Methodsmentioning
confidence: 99%
“…Their models were actively adopted to predict feature scale profiles of planar-type Si gate, Si fin of FinFET, trench, and hole etching for various kinds of films and plasmas such as Si (Cl2/Ar mixture), SiO2, SiN (normalC2normalF6, CHF3, and normalC4normalF8/normalO2/Ar mixtures), SiOCH (He/normalH2 and Ar/normalO2 mixtures), and HfO2 (Ar/BCl3/Cl2 and Ar/normalO2 mixtures) 51 59 As for HARC etching, the mechanism of the 3D SiO2 HARC feature distortion during normalC4normalF8/normalO2/Ar plasma etching with a CCP reactor was discussed in the cases of symmetric and asymmetric patterns (…”
Section: Modeling Methods For Etching Processmentioning
confidence: 99%
“…They demonstrated surface roughening and rippling during Si etching by Cl plasmas by considering the surface reactions in detail and proposed a mechanism for these reactions that take into account the variations in ion incident angle and gas flux ratio. Kushner and coworkers [58][59][60][61][62][63][64] have developed 2D models, not only for Si and SiO 2 films, but also for other kinds of films such as low-k (SiOCH) and metal (TiN=HfO 2 ) films using the gas and vacuum ultraviolet (VUV) radiation fluxes that were derived from the HPEM and showed the etched profiles as functions of the etching parameters in detail. 3D simulations of contact etching by the Bosch process, in which the cycles of etching and deposition are repeated, have also been proposed using a voxel model by Ertl and Selberherr, 70) and Sun et al 71) There are several other researchers on 3D feature scale profile simulations for Si and SiO 2 etching, including Kawai, 72) Moroz, 73) and Zhang and Kushner.…”
Section: Introductionmentioning
confidence: 99%
“…So far, many studies has been made on achieving high selectivity of high-k materials to SiO 2 and Si. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Among them, BCl 3 -based plasma has been extensively studied with various high-k materials such as HfO 2 4,7,[10][11][12] and ZrO 2 14,16,17) to obtain the high etch selectivity of high-k materials to SiO 2 and Si. The mechanism of highly selective etching of high-k materials to Si and SiO 2 using BCl 3 plasma is considered to be as follows.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, high etch selectivity of high-k materials to Si and SiO 2 is achieved in BCl 3 plasma. 7,[10][11][12]16) Concerning Hf-or Zr-based conventional high-k materials, many studies have been reported, as mentioned above. However, for lanthanum compounds, only a few studies have so far been carried out, although it has been reported that lanthanum compounds are difficult-to-etch materials.…”
Section: Introductionmentioning
confidence: 99%